2021
DOI: 10.3390/genes12040502
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal RNA Transcription Regulation in Breast Cancer

Abstract: Ribosome biogenesis is a complex process that is responsible for the formation of ribosomes and ultimately global protein synthesis. The first step in this process is the synthesis of the ribosomal RNA in the nucleolus, transcribed by RNA Polymerase I. Historically, abnormal nucleolar structure is indicative of poor cancer prognoses. In recent years, it has been shown that ribosome biogenesis, and rDNA transcription in particular, is dysregulated in cancer cells. Coupled with advancements in screening technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 136 publications
0
25
0
Order By: Relevance
“…3C ). Ribosomal biogenesis is a target for cancer therapy [ 28 ]. A total of 33 ribosome-associated genes were upregulated by DATS treatment ( Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3C ). Ribosomal biogenesis is a target for cancer therapy [ 28 ]. A total of 33 ribosome-associated genes were upregulated by DATS treatment ( Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The reason for this discrepancy is unclear. Evidence continues to accumulate to implicate ribosomal biogenesis in cancer [ 28 , 32 - 34 ]. As an example, increased ribosomal biogenesis was shown to attenuate the expression and activity of p53 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most notable findings in this research is that the ribosome pathway was found to be more frequently associated with the gene regulation of TSGs than non-TSGs in the downregulated genes. Ribosome is a critical cellular component for protein synthesis, and dysregulation of ribosome biogenesis was found to be associated with progression of breast cancer cells [ 43 , 44 , 45 ]. Since the ribosomal RNA or protein modifications affect cancer development [ 46 , 47 ], it is possible that differential regulations of ribosomal genes might influence cancer cell development via TSGs.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors of topoisomerase I activity, specifically camptothecin, irinotecan, and topotecian can also efficiently disrupt pol I transcription [ 134 , 135 ]. Now the rDNA and its functions are becoming a specific target of the anti-cancer therapy [ 136 ]. The first of the designed drugs is CX-3543 (quarfloxin), it specifically inhibits the elongation stage of pol I transcription by preventing the stabilizing interactions between nucleolin and G-quadruplexes in the rDNA gene.…”
Section: Ribosomal Dna and Cancer Therapymentioning
confidence: 99%